Financial Opening, Deposit Insurance, and Risk in a Model of Banking Competition - Cordella, Tito.; Levy Yeyati, Eduardo (Washington, D.C. : International Monetary Fund, 1998)
This paper studies the impact of competition on the determination of interest rates and banks' risk-taking behavior under different assumptions about deposit insurance and the dissemination of financial information. It finds that lower entry costs foster competition in deposit rate sand reduce banks' incentives to limit risk exposure. Although higher insurance coverage amplifies this effect, two alternative arrangements (risk-based contributions to the insurance fund and public disclosure of financial information) help to reduce it. Moreover, uninsured but fully informed depositors and risk-based full deposit insurance yield the same equilibrium risk level, which is independent of entry costs. The welfare implications of the different arrangements are also explored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet